(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
The small mammals collection described in the present paper has been collected during three field small excavation at the Upper Pleistocene site of Cava Salnova (Saltrio - VA -). The collection consists of 501 determined remains of small mammals coming from all 17 stratigraphical levels and belonging at least to 26 species. Two 14C datings (AMS) has been made on small mammals bones belonging to the lev. 1b: 1- 34315 ± 200 yr BP; 2- 35101± 250 yr BP. The interpretation of faunal data enables us to propose the following palaeoenvironmental framework: lower levels, lev. b and liv. c, are characterized by a cool weather with a high degree of plant cover. The deposition of lev. e to the lev. g coincided with an important reforestation occurred at the same time of the hottest Wurmian interpleniglacial. In lev. m, n, o, the snow vole, although rare, reappears. This may indicate the beginning of the climatic cooling, which is the prelude to the Last Glacial Maximum.